Annotated Catalogue Of Batik Paintings By Basu Swastha Dharmmesta 1968 – 2021 - Syafina Zahra Yanurifa; Trisna Pradita Putra; Dian Ajeng Kirana (TUMATA: Journal of Arts and Cultural Management, 2023)
Basu Swastha Dharmmesta has been making painted batik for approximately 53 years but has never been systematically archived and organized. This problem encourages researchers to start cataloging and archiving Basu Swastha Dharmmesta's works to produce an annotated catalog. Cataloging uses an aesthetic approach, and data collection uses qualitative methods. The annotated catalog is a semi-active dynamic archive containing detailed information about the artist, both in academia and art. This catalog measures 33x21cm and contains 104 batik paintings by Basu Swastha Dharmmesta during his 53 years of work. Making the annotated catalog consists of several stages: licensing and consultation with the supervisor, collecting data and materials, interviewing the artist, taking documentation of artworks and academic works, compiling materials and information, and making the design and packaging of the annotated catalog. The documentation archive in the form of this annotated catalog can be an authoritative reference for the public to know the academic works and batik paintings of Basu Swastha Dharmmesta and be able to become an authoritative reference.